Estruturas de governança em Arranjos Produtivos Locais - Queiroz, Timóteo Ramos [UNESP] (Universidade Católica Dom Bosco, 2013)
This study aimed to evaluate the forms of governance among enterprise presents in Local Productive Arrangements (APL), so analyzing the performance of cooperation activities or hierarchies. This research was based on an exploratory study in the background theories about networks and asymmetries of power, and after that, a empirical observation of APLs footwear from Birigui, Franca and Jaú. It was possible to evidence the forms of governance in each APL supported by taxonomy from Storper and Harrison (1991). The paper contributed mixing the network typology with a cross sectional analysis from Birigui, Franca and Jaú.

Este estudio tuvo como objetivo evaluar las formas de gobierno entre las empresas que operan en Arreglos Productivos Locales (APL), para analizar el desempeño de actividades de cooperación o las jerarquías. Esta investigación se basó en un estudio exploratorio sobre las teorías de las redes y las asimetrías de poder, y después de eso, una observación empírica de los clusters de calzado Birigui, Franca y Jau. Fue posible observar las formas de gobierno en cada una taxonomía de APL con el apoyo de Storper y Harrison (1991). El trabajo aportado por la mezcla del tipo de red con una comparación entre los grupos de Birigui, Franca y Jau.

Cette étude visait à évaluer les formes de gouvernance entre les entreprises locales dans les arrangements productifs (APL), pour analyser la performance des activités de coopération ou des hiérarchies. Il a été réalisé une étude exploratoire sur les théories des réseaux et des asymétries de pouvoir, et après cela, une observation empirique des grappes de chaussures Birigui, la Franca et Jau. Il était possible d'observer les formes de gouvernance dans chaque APL, la taxonomie de Storper et Harrison (1991). Le travail a contribué à l'aide du type de réseau avec une comparaison entre les groupes de Birigui, la Franca et Jau.

Este estudo teve como objetivo avaliar as formas de governança entre empresas em Arranjos Produtivos Locais (APL), para analisar o desempenho das atividades de cooperação ou hierarquias. Foi feito um estudo exploratório nas teorias sobre as redes e assimetrias de poder e, depois disso, uma observação empírica dos APLs de calçados de Birigui, Franca e Jaú. Foi possível constatar as formas de governança em cada APL, pela taxonomia de Storper e Harrison (1991). O trabalho contribuiu utilizando a tipologia de rede com uma análise entre os APLs de Birigui, Franca e Jaú.
Forms of governance in Local Productive Arrangemens
Las estructura de gobernanza en los Arreglos Productivos Locales
Keywords: Local Productive Arrangements; Governance Structure; Footwear; Arranjo Produtivo Local; Estrutura de governança; Calçados